Novel Scratch Programming Blocks for Web Scraping - Park, Youngki; Shin, Youhyun (Electronics (Basel), 2022)
Although Scratch is the most widely used block-based educational programming language, it is not easy for students to create various types of Scratch programs based on real-life data because it does not provide web scraping capabilities. In this paper, we present novel Scratch blocks for web scraping. Using these blocks, students can not only scrape the contents of HTML elements in a web page by using CSS selectors but also automate their keyboard and mouse in a number of ways, such as by using XPaths, the coordinates of the mouse, input strings, keys, or hot keys. We also present file access blocks that allow students to easily store and retrieve the scraped data in the form of key–value pairs. We conducted two lectures for a total of 15 primary/secondary school (K-12) teachers, allowing them to make ten web scraping example applications. As a result of a survey of the teachers, the proposed web scraping blocks achieved high scores for all evaluation measures.